Applicability of processability theory to Japanese adolescent EFL learners: A case study of early L2 syntactic and morphological development. (August 2015) - Eguchi, Akiko; Sugiura, Masatoshi
Abstract: Processability theory (PT) predicts that all L2 learners follow fixed developmental schedules due to psycholinguistic constraints, accounting for the development of syntax and morphology within the same framework. Recent studies, however, report some counterevidence on morphological development. The theory has not been tested sufficiently in EFL contexts. This study examined the applicability of PT to Japanese adolescent EFL learners. Through four communicative tasks, we elicited spontaneous spoken data from 14 Japanese secondary students and cross-sectionally analyzed 15 syntactic and 6 morphological structures using implicational scaling. The study identified four major findings. First, PT prediction is applicable to early EFL learning. Second, there are two different developmental paths and language learners' syntactic development tends to emerge before morphological development. Third, morphological development, particularly phrasal plural-marking, is not always well-mapped to PT prediction. Fourth, formulae seem to play an important role in scaffolding productive use of grammatical structures. These findings indicate that PT needs to be modified to account for the developmental gap between syntax and morphology. They also suggest that L2 instructors should consider language learners' morphological development more in task-based language teaching. Further research should include elaborate analyses of morphological development and the role of formulae in acquiring grammatical structures.